Assessment of leucaena leucocephala for in vivo anti-diabetic and antioxidant effects in streptozocin-induced diabetic rats / Nooriza Azaman - Nooriza, Azaman (2013)
Leucaena leucocephala (Lam.) deWit (Leguminosae) also known as 'Petang Belalai' is a fast growing shrub or tree found in tropical and subtropical areas. Its fruit has been consumed as food by people in Malaysia, Thailand, Philipines, Indonesia and Mexico. In Indonesia and Mexico the fruits have been used to treat diabetes.